Integration of Solar PV Panels in Electric Vehicle Charging Infrastructure: Benefits, Challenges, and Environmental Implications - Abhishek Kumar Tripathi; G. Sree Lakshmi; Heena Mishra; Shravani Chapala; Mamdooh Alwetaishi; Farruh Atamurotov; Natei Ermias Benti; Sreekanth Sura; C. Ahamed Saleel (Energy Science & Engineering)
ABSTRACT The urgent need for sustainable transportation has highlighted the integration of solar photovoltaic (PV) panels into electric vehicle (EV) charging infrastructure. This review examines the benefits, challenges, and environmental impacts of this integration. The paper begins by exploring the role of large‐scale solar electric vehicles, featuring cost‐effective, flexible thin‐film solar cells embedded in vehicle body panels. Extensive simulations in various climates demonstrate their potential to address EV charging concerns, reduce range limitations, and manage intermittent energy generation. The review then focuses on Japan's leadership in renewable energy, analyzing the integration of PV power into future electricity systems. Scenario analysis reveals the synergy between renewables, EVs, and heat pumps, supported by smart control strategies, indicating a sustainable energy future for Japan. The final analysis shifts to the Netherlands, where integrating PV panels with workplace EV charging shows promise both economically and environmentally. Economic assessments confirm the feasibility of this approach, supported by installation methods and feed‐in tariffs. Overall, the review highlights the transformative potential of solar PV integration in EV charging infrastructure while acknowledging technical and grid integration challenges. It calls on researchers, policymakers, and industry stakeholders to collaborate in advancing sustainable, efficient, and environmentally friendly urban transportation systems.